2002
DOI: 10.1177/014860710202600613
|View full text |Cite
|
Sign up to set email alerts
|

North American Summit on Aspiration in the Critically Ill Patient: Consensus Statement

Abstract: Aspiration is the leading cause of pneumonia in the intensive care unit and the most serious complication of enteral tube feeding (ETF). Although aspiration is common, the clinical consequences are variable because of differences in nature of the aspirated material and individual host responses. A number of defense mechanisms normally present in the upper aerodigestive system that protect against aspiration become compromised by clinical events that occur frequently in the critical care setting, subjecting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
202
0
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 260 publications
(217 citation statements)
references
References 0 publications
3
202
0
12
Order By: Relevance
“…The rationale for measurement of GRVs is to reduce the risk for aspiration pneumonia by either ceasing or modifying the enteral feeding strategy based on the detection of excess gastric residuals. The inherent controversy is that observational and interventional studies have not consistently confirmed a relationship between the measurement of GRVs (with thresholds ranging from 200 mL to no monitoring of GRVs) and outcomes of vomiting, aspiration, or pneumonia [597][598][599][600][601][602][603]. In our systematic review, we identified one multicenter non-inferiority trial of 452 critically ill patients who were randomized to not monitoring GRVs versus monitoring GRVs at 6-h intervals [602].…”
Section: We Recommend Against the Use Of Omega-3 Fattymentioning
confidence: 99%
“…The rationale for measurement of GRVs is to reduce the risk for aspiration pneumonia by either ceasing or modifying the enteral feeding strategy based on the detection of excess gastric residuals. The inherent controversy is that observational and interventional studies have not consistently confirmed a relationship between the measurement of GRVs (with thresholds ranging from 200 mL to no monitoring of GRVs) and outcomes of vomiting, aspiration, or pneumonia [597][598][599][600][601][602][603]. In our systematic review, we identified one multicenter non-inferiority trial of 452 critically ill patients who were randomized to not monitoring GRVs versus monitoring GRVs at 6-h intervals [602].…”
Section: We Recommend Against the Use Of Omega-3 Fattymentioning
confidence: 99%
“…Adequate numbers to make comparisons between groups were attained only with the 30-degree cut-point. Because published guidelines to prevent aspiration and pneumonia call for head-ofbed elevation to at least 30 degrees (16,17), this value was used to make group comparisons. As shown in Table 8, a mean backrest elevation <30 degrees occurred more often in the highaspiration group than in the low-aspiration group (67.6% vs. 56.0%, respectively; p = .024).…”
Section: Effect Of Aspiration and Pneumonia On Use Of Hospital Resourcesmentioning
confidence: 99%
“…Este proceso dio como resultado una supresión por repetición de casi un 30% de los trabajos; y finalmente se listaron 29 artículos a localizar en texto completo 6,11,14, .…”
Section: Resultsunclassified
“…McClave et al 14 presentan una exhaustiva revisión acerca del problema de la aspiración en las poblaciones de paciente crítico, y entre otros temas abordan la relación con el VGR y recomiendan la reintroducción del contenido aspirado en pacientes portadores de nutrición enteral 14 .…”
Section: Análisis Descriptivounclassified
See 1 more Smart Citation